Artificial Intelligence dan (Persoalan tentang) Pekerjaan: Sebuah Tinjauan Filosofis dari Perspektif Vita Activa Hannah Arendt - Dhedhe, Ferdinandus; Yanto Nahak, Antonius Redy (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Artificial Intelligence AI is the result of innovation and the proficiency of human technology. Technology like (AI) has the power to change humans including in terms of ability, expertise, time and handwork. This is the dilemmatic aspect of the emergence of AI. This article aims to examine the real technological developments and human innovations in AI and their impact on human handwork as a model of self-realization. The author analyzed this problem using a literature review method related to the Vita Activa concept initiated by Hannah Arendt. Starting from Arendt's criticism of the devaluation of the value of human action by the presence of AI, this research will show that active human involvement in handiwork still has the value of realizing the existence of human abilities. Thus, amidst human anxiety about the presence of AI, Hannah Arendt affirms the importance of human involvement in the public sphere.Abstrak  Artificial Intelligence (AI) adalah hasil inovasi dan kecakapan teknologi manusia. Teknologi seperti ini (AI) memiliki daya mengubah manusia termasuk dalam hal kemampuan, keahlian, waktu dan kerja tangan. Inilah aspek dilematis dari kemunculan AI. Tulisan ini bertujuan untuk mengkaji perkembangan teknologi dan inovasi manusia yang nyata dalam AI dan impaknya terhadap kerja tangan manusia sebagai satu model perwujudan dirinya. Persoalan ini dianalisis penulis dengan menggunakan metode kajian pustaka terkait konsep Vita Activa yang digagas oleh Hannah Arendt. Bertolak dari kritik Arendt terhadap devaluasi nilai tindakan manusia oleh kehadiran AI, penelitian ini hendak memperlihatkan bahwa keterlibatan aktif manusia dalam karya tangan tetap memiliki nilai pengejawantahan eksistensi kemampuan manusia. Dengan demikian, di tengah kecemasan manusia akan kehadiran AI, Hannah Arendt mengafirmasi pentingnya keterlibatan manusia di dalam ruang publik (public sphere).